Cluster approach to sustainable tourism development: Pendekatan kluster untuk pengembangan pariwisata berkelanjutan - Ravshan Allayorov (Academia Open, 2019)
The article considers the cluster approach to the sustainable development of tourism destinations. The concept of the "regional tourism cluster" and its features, as well as the symbol of the formation of the tourist group.